2004
DOI: 10.1098/rstb.2004.1566
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the rigor complex and its implications for the power stroke

Abstract: Decorated actin provides a model system for studying the strong interaction between actin and myosin. Cryo-energy-filter electron microscopy has recently yielded a 14 Å resolution map of rabbit skeletal actin decorated with chicken skeletal S1. The crystal structure of the cross-bridge from skeletal chicken myosin could not be fitted into the three-dimensional electron microscope map without some deformation. However, a newly published structure of the nucleotide-free myosin V cross-bridge, which is apparently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
145
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(150 citation statements)
references
References 32 publications
5
145
0
Order By: Relevance
“…However, only the deletion of D590 affected the basal ATPase, which was elevated almost 10-fold. Structural studies have shown that D590 (D570 in chicken myosin-V) experiences the largest conformational changes upon cleft closure, when the region undergoes a helix-to-loop transition [24,65,117,118].…”
Section: Strutmentioning
confidence: 99%
“…However, only the deletion of D590 affected the basal ATPase, which was elevated almost 10-fold. Structural studies have shown that D590 (D570 in chicken myosin-V) experiences the largest conformational changes upon cleft closure, when the region undergoes a helix-to-loop transition [24,65,117,118].…”
Section: Strutmentioning
confidence: 99%
“…It corresponds to the ATP-state of the motor that detaches from actin at the end of the cross-bridge cycle. Only the recently published myosin V nucleotide-free structure has a closed cleft (Coureux et al 2003) necessary for strong actin binding, and thus it fits even the myosin II cryoEM maps better than the myosin II post-rigour structures (Holmes et al 2004).…”
Section: Actin-myosin Complex and The Swingingmentioning
confidence: 99%
“…(Compare the docking of post-rigour in figure 2 with the docking of rigour in figure 8. More detail is given in the contribution to this issue by Holmes et al (2004).) This movement is necessary to generate a strong binding interface with actin, as myosin in the post-rigour conformation binds weakly to actin.…”
Section: Actin-myosin Complex and The Swingingmentioning
confidence: 99%
“…the weak to strong transition states associated with the AÁMccÁDÁP to AÁMocÁDÁP transition (Bershitsky et al 1997). More recently, Holmes et al (2004) have suggested a structural model in which the strong binding of actin allows the lever arm to swing without the opening of switch 2. While this model provides another mechanism for avoiding futile cycling, our data with ATPcS lend no support for this idea, as will be discussed elsewhere (Conibear et al 2004).…”
Section: Correlation Of Myosin Movements To Thementioning
confidence: 99%